Justice and Justice: A Study of the Role of Judges in Answering Society's Need for a Fair Law - Taqwanda Aulia Mahfud; M. Syahrul Borman (Journal of Law, Politic and Humanities, 2025)
Abstract: Law enforcement in Indonesia still faces serious challenges in realizing substantive justice for all levels of society. Inequality in the implementation of the law is often seen in the tendency of the justice system to be more repressive towards the lower classes, while structural crimes such as corruption are difficult to touch optimally. This study investigates the strategic position of judges in addressing society’s demand for equitable law, utilizing a normative juridical lens supported by the Systematic Literature Review (SLR) method. The findings suggest that judges are not merely executors of legal norms, but autonomous agents tasked with interpreting and embodying the living values of justice within society. As Friedman posits, the synergy among legal substance, structure, and culture is essential to ensure the law operates effectively within its sociocultural context. Judges are required to have integrity, professionalism, and social sensitivity in shaping decisions that reflect justice, not mere formal legality. Thus, a judicial paradigm reform is needed to ensure that the law becomes a tool for just and civilized social transformation.